Industrial Capacity and Economic Development: The Role of Institutional Quality and Monetary Policy in Nigeria - Courage Ose Eburajolo; Ewere F Okungbowa (Faculty of Economics, Universitas Sriwijaya, 2026)
The moderating effect of the two variables, namely institutional quality and monetary policy, in the link between manufacturing sector performance and economic development in Nigeria between the period 2000Q1 and 2024Q4, have been investigated in this study. The results from the use of the ARDL framework to the quarterly time series data indicates that the path dependent growth theories are supported by the findings, since economic development from the past has significant impact on the current economic development. The manufacturing sector has a positive and statistically significant impact on the Human Development Index (HDI). Of particular interest, real interest rates exhibit a stronger effect on economic development via the manufacturing sector channels than broad money supply (M2). The institutional quality variable (regulatory quality) does not have a statistically significant moderating effect, indicating a lack of institutional quality in implementing governance in developing economies. The results support the Rostow's stage theory as these findings quantify the intertemporal spillover effects of development and shed light on monetary policy transmission heterogeneity in the endogenous growth field. There is a special focus on interest rate targeting to stimulate manufacturing investment andinstitutional mechanisms to guarantee developmental continuity in policy recommendations.